The Impact of Climate Change on the Value of Growing Maize as a Biofuel - Sally Olasogba; Les Duckers (The Central European Review of Economics and Management (CEREM), 2020)
Aim: According to COP23, Climate Change threatens the stability of the planet's ecosystems, with a tipping point believed to be at only +2°C.~ With the burning of fossil fuels, held responsible for the release of much of the greenhouse gases, a sensible world- wide strategy is to replace fossil fuel energy sources with renewable ones. The renewable resources such as wind, hydro, geothermal, wave and tidal energies are found in particular geographical locations whereas almost every country is potentially able to exploit PV and biomass. This paper examines the role that changing climate could have on the growing and processing of biomass. The primary concern is that future climates could adversely affect the yield of crops, and hence the potential contribution of biomass to the strategy to combat climate change. Maize, a C4 crop, was selected for the study because it can be processed into biogas or other biofuels. Four different Nigerian agricultural zones growing maize were chosen for the study. Long-term weather data was available for the four sites and this permitted the modelling of future climates. Design / Research methods: The results of this study come from modelling future climates and applying this to crop models. This unique work, which has integrated climate change and crop modelling to forecast yield and carbon emissions, reveals how maize responds to the predicted increased temperature, change in rainfall, and the variation in weather patterns. In order to fully assess a biomass crop, the full energy cycle and carbon emissions were estimated based on energy and materials inputs involved in farm management: fertilizer application, and tillage type. For maize to support the replacement strategy mentioned above it is essential that the ratio of energy output to energy input exceeds 1, but of course it should be as large as possible. Conclusions / findings: Results demonstrate that the influence of climate change is important and in many scenarios, acts to reduce yield, but that the negative effects can be partially mitigated by careful selection of farm management practices. Yield and carbon footprint is particularly sensitive to the application rate of fertilizer across all locations whilst climate change is the causal driver for the increase in net energy and carbon footprint at most locations. Nonetheless, in order to ensure a successful strategic move towards a low carbon future, and sustainable implementation of biofuel policies, this study provides valuable information for the Nigerian government and policy makers on potential AEZs to cultivate maize under climate change. Further research on the carbon footprint of alternative bioenergy feedstock to assess their environmental carbon footprint and net energy is strongly suggested. Originality / value of the article: This paper extends the review on the impact of climate change on maize production to include future impacts on net energy use and carbon footprint using a fully integrated assessment framework. Most studies focus only on current farm energy use and historical climate change impact on farm GHG emissions.~
Keywords: 330